2017
DOI: 10.1371/journal.pone.0177614
|View full text |Cite
|
Sign up to set email alerts
|

Predictive models of poly(ethylene-terephthalate) film degradation under multi-factor accelerated weathering exposures

Abstract: Accelerated weathering exposures were performed on poly(ethylene-terephthalate) (PET) films. Longitudinal multi-level predictive models as a function of PET grades and exposure types were developed for the change in yellowness index (YI) and haze (%). Exposures with similar change in YI were modeled using a linear fixed-effects modeling approach. Due to the complex nature of haze formation, measurement uncertainty, and the differences in the samples’ responses, the change in haze (%) depended on individual sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 50 publications
(42 reference statements)
0
15
0
Order By: Relevance
“…Broad absorption appears to be a superposition of several bands attributed to oxidation products. The shape of the spectrum is very similar to that one presented by Gok et al . for photodegraded PET.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Broad absorption appears to be a superposition of several bands attributed to oxidation products. The shape of the spectrum is very similar to that one presented by Gok et al . for photodegraded PET.…”
Section: Resultsmentioning
confidence: 99%
“…These species cause yellowing of the polymer due to their strong absorbance and the characteristic long‐wavelength tail in the visible region. Usually, the proposed mechanism starts with hydroxylation of the terephthalic ring, which leads to conjugated aromatic systems through cumulative oxidation …”
Section: Resultsmentioning
confidence: 99%
“…In this degradation science study, the epidemiological data science approach was applied in a laboratory‐based, randomized, longitudinal study design . Samples of unstabilized PET films (Dupont‐Teijin Melinex 454, 75 μm) were randomly assigned to exposure conditions and followed over time with repeated measurements.…”
Section: Methodsmentioning
confidence: 99%
“…Introducing a high level of UV photostabilizers to polyester through a co‐extrusion process was found to be useful in making polymers highly resistant to weathering‐induced changes . It was shown that polymer longevity in outdoor applications can be enhanced by using UV photostabilizers based on benzoxazinone, triazines, hydroxybenzophenones, hydroxyphenyl benzotriazole and mixtures, quenchers, and radical scavengers . The chemical family and substituents play a key role in UV absorber properties and performance …”
Section: Introductionmentioning
confidence: 99%